RESPON MASYARAKAT TERHADAP KEBIJAKAN RELOKASI PADA KAWASAN RAWAN BENCANA (KRB) (Studi Kasus: Relokasi Desa Glagaharjo) - , DIAN AYUNINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research describe the analysis of the differences in the response by the public in the relocation of settlements located in disaster-prone areas of Mount Merapi. This study aims to find differences in the response for the emergence of relocation policy in response to the relocation of policy target groups in disaster-prone areas Glagaharjo villagers. This study used a descriptive research method with a qualitative approach. This research will explain the differences in the way and viewpoints from the public in response to the relocation policy. The locus of this study is on the whole territory Glagaharjo village located in disaster-prone region III of Merapi Mountain. Sources of data used in this study are primary and secondary data. Data collection techniques used is by interview and documentation. From the research conducted it can be concluded that the implementation of the relocation policy on disaster-prone areas, there are differences in the response shown by the people in the village Glagaharjo as one target group policy. The difference in the attitude of the community's relocation policy to respond to them due to the clarity/understanding people's relocation policy, the scope of the public demanded a change of the policy of relocation, as well as the social and cultural conditions. Differences in responses for and against relocation policy can be seen from the difference in assessment, attitudes, and actions between each target group policy. Society of the pro-rate the policy of relocation policy is advantageous because in addition they have a residence in a secure location, land long they can still be used. While the action shown each target group is the target group of the cons is to rebuild permanent housing located in disaster-prone areas. In addition they also put up some banners rejection relocations in their village, and also by way of demonstration to resist relocation. To avoid misunderstandings between the government and the public communication should be dissemination of relocation policy and open dialogue should be further improved. By socializing more often it will have an impact on the level of public acceptance of the policy content clearer.